Effects of Dispositional and Instructional Time Perspective on Academic Performance and Motivations Among Primary School Students: A Concordance Hypothesis - Li, Kin-Kit; Yip, Hiu Yan Vincy; Wong, Yuen Shan Noel (Frontiers in Education, 2021)
Background: Dispositional future time perspective (FTP) has been acknowledged for its benefits on academic outcomes. Lacking in the literature are 1) understanding of FTP in children, 2) experimental studies, and 3) evidence for time perspective concordance (i.e., matching between dispositional and instructional FTP yield favorable outcomes). Aims: Therefore, this study examined whether dispositional FTP, instructional FTP, and their interaction were associated with academic outcomes including reading performance and academic motivations among primary school students. Sample: The participants were grade-2 or grade-3 Hong Kong students (N=92; Age: M=8.05, SD=0.72; 45% girls). Methods: The participants rated their dispositional FTP and were randomly assigned to draw a picture of their future or present self with the assumption that they study hard. The students then completed a reading task and rated their intrinsic motivation, extrinsic motivation, and amotivation. Results: Better reading scores were found in future-oriented students who drew a future self and those less future-oriented who drew a present self. No concordance effects were found on motivations. Nevertheless, the future-drawing task led to a greater extrinsic motivation than the present-drawing task. Conclusions: Some children may have developed FTP in their middle childhood. Academic motivations may be more malleable at a younger age. When facing incongruent instructional context, more cognitive resources may be drained to resolve the dissonance and, thus, compromise the cognitive performance. Rather than a predominant focus on future achievements, a balanced emphasis on present and future or a temporally tailored instructional context for individuals may be considered in primary education.